The Role of Fiqh Iqtishad in Developing Islamic Economic Law and Practice - Yuly Rusmariani (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
Fiqh Iqtishad, as a branch of Islamic jurisprudence that regulates economic behavior, plays a pivotal role in the development of Islamic economic law and practice. In the face of modern economic complexities, this study investigates how fiqh iqtishad provides a normative and ethical foundation for sharia-compliant economic systems. This research employs a qualitative library research method, collecting and analyzing authoritative sources including classical texts, academic journals, and regulatory frameworks. The study reveals that fiqh iqtishad serves not only as a source of legal guidance, but also as a dynamic and adaptable instrument for economic transformation grounded in the Qur’an, Hadith, ijmaʿ, and qiyas. Key principles such as the prohibition of riba, gharar, and maysir, as well as the emphasis on justice, transparency, and equitable distribution through zakah and waqf, demonstrate its integrative capacity in addressing both spiritual and material aspects of economic life.The findings show that while fiqh iqtishad has significantly influenced Islamic banking, halal investment, and wealth redistribution, its implementation still faces challenges, particularly in the areas of public awareness, regulatory harmonization, and institutional capacity. This study concludes that strengthening the application of fiqh iqtishad requires collaborative efforts between scholars, regulators, and practitioners to realize a more just, inclusive, and sustainable Islamic economic system.Keywords: Fiqh iqtishad; Islamic economic law; sharia finance; justice; wealth distribution